Challenges in the Management of Hemophilia B with Inhibitor - Batorova, Angelika; Morongova, Anna; Tagariello, Giuseppe; Jankovicova, Denisa; Prigancova, Tatiana; Horakova, Julia (Seminars in Thrombosis and Hemostasis, 2013)
Development of factor IX (FIX) inhibitor is a rare but challenging complication in hemophilia B. In addition to inefficacy of specific replacement therapy, FIX inhibitors increase morbidity due to serious allergic reactions/anaphylaxis upon treatment with FIX. Limited experience with immune tolerance induction (ITI) shows a high risk of nephrotic syndrome development and poor ITI outcomes. Recently, immunomodulation therapy has been used in ITI regimens in hemophilia B; however, relevant guidelines for ITI in hemophilia B are still lacking. We describe a 7-year-old hemophilia B patient with “null” mutation Arg29 stop who underwent surgery and massive transfusion therapy in the neonatal period and developed an FIX inhibitor after consecutive 20 exposures to FIX concentrate. At the age of 6 years, a high-dose ITI was commenced combined with immunomodulation therapy including rituximab, dexamethasone, and intravenous immunoglobulin. Allergic reactions that occurred in the third week of ITI were resolved by premedication with antihistamines and continued immunomodulation protocol without any need for ITI interruption. Inhibitor was negative from week 10; however, doses of FIX continued unchanged until pharmacokinetic criteria for success were met at month 9 of ITI. One year after the start of ITI, the patient started regular prophylaxis with FIX 41 IU/kg three times a week. No further allergic reactions or any signs of nephrotic syndrome have occurred.
Keywords: hemophilia B; FIX inhibitor; allergic reactions; immune tolerance induction; immunomodulation therapy; rituximab